Yttrium-90 radioembolization as an in vivo immune modulator: clinical evidence and pharmacologic implications - Tang, Shiwei; Cai, Jia; Wu, Pandi; Wang, Guanwu (Frontiers in Pharmacology, 2026)
Yttrium-90 (Y-90) transarterial radioembolization (TARE) is widely used for the treatment of primary and metastatic liver tumors and has traditionally been viewed as a purely locoregional radiotherapeutic modality. However, accumulating clinical evidence supports the concept that Y-90 TARE can induce measurable immunologic changes in patients, detectable both systemically and within the tumor microenvironment. Longitudinal analyses of peripheral blood and tumor tissue from patients with hepatocellular carcinoma and liver metastases demonstrate transient immune activation, myeloid remodeling, and adaptive immune perturbations following treatment. Notably, these immune-stimulatory signals may coexist with counter-regulatory mechanisms, including upregulation of immune checkpoint pathways, suggesting a dynamic balance between immune priming and adaptive resistance. In this Perspective, we synthesize available in vivo human evidence supporting the concept that Y-90 TARE functions as an immune modulator rather than a solely cytotoxic intervention. We discuss the pharmacologic implications of these findings, particularly in relation to treatment sequencing, biomarker development, and rational combination strategies with immunotherapies. Recognizing Y-90 TARE as an immunologically active modality may inform the design of future clinical trials and optimize its integration into combination regimens aimed at durable tumor control.